All Days 2010
DOI: 10.2118/140676-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Entrepreneurship Development and Corporate Social Responsibility as Strategies for Conflict Resolution in the Niger-Delta region in Nigeria

Abstract: The Niger Delta undoubtedly is the oil fountain of Nigeria. The region comprises of nine oil rich states of Abia, Akwa Ibom, Bayelsa, Cross River i , Delta, Edo, Imo, Ondo, and Rivers. The region's oil accounts for approximately 90 percent of the value of Nigeria's exports, but remains one of the least developed regions as a result of deliberate neglect. The neglect of the region for many years by successive governments in Nigeria degenerated into violent political crisis and armed conflict, which began to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It is evident from the negative impact of solid wastes and effluents in different parts of the world that CSR programmes of companies do not align with the goals of SD. Environmental sustainability literature in Nigeria indicated that ecosystem abuses and other irresponsible social actions of Shell, Chevron and ExxonMobil precipitated the acts of militancy, hostage taking and vandalism of plants in the South-South of Nigeria (Raimi and Adeleke, 2010;Raimi et al, 2013).…”
Section: Theoretical Framework and Hypotheses Formulationmentioning
confidence: 99%
“…It is evident from the negative impact of solid wastes and effluents in different parts of the world that CSR programmes of companies do not align with the goals of SD. Environmental sustainability literature in Nigeria indicated that ecosystem abuses and other irresponsible social actions of Shell, Chevron and ExxonMobil precipitated the acts of militancy, hostage taking and vandalism of plants in the South-South of Nigeria (Raimi and Adeleke, 2010;Raimi et al, 2013).…”
Section: Theoretical Framework and Hypotheses Formulationmentioning
confidence: 99%
“…This fact was corroborated by Aduba (2011) reporting for the Akwa Ibom State government as saying that one of the major factors of restiveness in the Niger Delta region is high rate of unemployment. The traits of creativity, risk-loving, innovation, strategic thinking and constructive engagement against the government by discontented Nigerians could as well be directed to entrepreneurship development (Raimi, 2010). According to Onyeneho & Ezeano( 2011) development is a process by which individuals in a community or country improve their economic and social wellbeing.…”
Section: Nexusmentioning
confidence: 99%
“…As such, the system destroyed self-reliance, self-employment and entrepreneurial skills of Nigerians as they became permanently dependent on the colonial masters (Nicks, 2008;Raimi & Adeleke, 2010). This led to massive unemployment and craze in the contemporary times for ready-made jobs, (Oladele, Akeke, & Oladunjoye, 2011).…”
Section: Introductionmentioning
confidence: 99%